Efficacy of montelukast and desloratadine combination in allergic rhinitis - Cingi, Cemal; Oğhan, Fatih; Ünlü, Halis; Tekat, Atilla; Okuyucu, Şemsettin (ENT Updates, 2011)
Allergic rhinitis represents a global health problem affecting 10 to 25% of the population worldwide. The complications i.e. sinusitis, nasal polyps, middle ear and lower respiratory tract infections increase the importance of allergic rhinitis. Besides treatment costs, due to wage loss and decrease in productive capacity it has a huge negative impact on community. It may also seriously affect quality of life. Despite recent developments in its treatment modalities, several studies have indicated that the prevalence of allergic rhinitis is increasing. New knowledge on the mechanisms underlying allergic inflammation of the airways has resulted in better therapeutic strategies for allergic rhinitis. Montelukast and desloratadine has powerful effects on allergic rhinitis. Since studies demonstrate that both products have better pharmacodynamic and pharmacokinetic profiles, and having side effects similar to placebo, they are better options for this sub-group. The concomitant use of both drugs is believed to provide a better control on the symptoms of allergic rhinitis. The combination therapy possibly provides a more potential reduction in early and late allergic and inflammatory response to histamine and histamine like mediators during allergen inhalation. Including a fixed dose combination of montolukast-desloratadine to the treatment strategy seems to be a more rational and cost effective approach in these groups of patients.